PARENTAL FEEDING PRACTICES AND CHILDREN’S DIETARY HABITS FOR NURTURING CARE AMONG STUNTED CHILDREN IN BOGOR REGENCY, INDONESIA - Fajrunni’mah, Rizana; Gunarti, Dwirini; Sadikin, Mohamad; Wibowo, Heri (Malaysian Journal of Public Health Medicine, 2025)
The issue of stunting, although it has generally decreased, is still accompanied by an elevated risk of morbidity and mortality. The Nurturing Care approach integrates five caregiving components, one of which is adequate nutritional fulfillment. However, there are not many publications that discuss this problem, including in Indonesia. The aim of study was to examine parental feeding practices and children’s dietary habits in stunted children. A case-control design was conducted on 80 participants consist of two groups: stunted and control children aged 24-36 months. Data were collected from structured questionnaires filled out by parents. Chi-square and mann-whitney analysis with statistical significance expressed at 95% CI were used. This study identified a substantial correlation between exclusive breastfeeding and the prevalence of stunting (p=0.02). There was no relationship between the age of introducing complementary feeding and the administration of multivitamins with the incidence of stunting. The score for providing an environment with healthy food in the stunting group was significantly lower (p=0.01) compared to the control group. Furthermore, the analysis revealed no correlation between children dietary habit and the occurrence of stunting in children. It shows that the importance of parents’ role in nurturing care for stunting. Adequate parental feeding practices especially in providing a healthy food environment should be apply early to prevent stunting.